Pleuroparenchymal Fibroelastosis: A New Entity within the Spectrum of Rare Idiopathic Interstitial Pneumonias. (26th August 2015) - Portillo, Karina; Guasch, Ignasi; Becker, Caroline; Andreo, Felipe; Fernández-Figueras, Maria Teresa; Ramirez Ruz, José; Martinez-Barenys, Carlos; García-Reina, Samuel; Lopez de Castro, Pedro; Sansano, Irene; Villar, Ana; Ruiz-Manzano, Juan
Abstract : Pleuroparenchymal fibroelastosis (PPFE) is a rare entity that has been recently included in the official American Thoracic Society/European Respiratory Society (ATS/ERS) statement in 2013 as a group of rare idiopathic interstitial pneumonias (IIPs). PPFE is characterized by pleural and subpleural parenchymal thickening due to elastic fiber proliferation, mainly in the upper lobes. The etiology of the disease is unclear, although some cases have been associated as a complication after bone marrow transplantation, lung transplantation (LT), chemotherapy, and recurrent respiratory infections. The patients usually report progressive dyspnea and dry cough and are predisposed to develop spontaneous or iatrogenic pneumothoraces after surgical lung biopsy (SLB) for its diagnosis. That is why better awareness with the clinical and radiologic features can help optimal management by the multidisciplinary team. Novel invasive techniques such as cryobiopsy may become useful tools in these patients as it could spare SLB. We present the first reported cases in Spain.